Trend of C-Reactive Protein and Erythrocyte Sedimentation Rate in Psoriatic Patients Under Treatment of Standard Protocol of Infliximab: - Zamanian, Abbas; Darvari, Seyyedeh Bahareh; Ehsani, Amir Houshang; Mehran, Golnaz; Azizpour, Arghavan (Galen Medical Journal, 2015)
Background: Psoriasis is a chronic and inflammatory dermatologic disease. Inflammatory biomarkers such as C-reactive protein (CRP) and Erythrocyte sedimentation rate (ESR) are known as immediate and delayed inflammatory biomarkers, respectively. Due to the fact that anti-inflammatory drugs such as Infliximab are widely used in psoriasis treatment, the aim of this study was to evaluate ESR, CRP and PASI scores in patients treated with Infliximab in a 24 week trend. Materials and Methods: This study was accomplished as a before-after study. Twenty seven psoriatic patients were included and standard Infliximab therapy was applied. All patients underwent 3 times of blood collection and in each session CRP, ESR and PASI scores were measured at the beginning of study and at the 12th and 24th weeks of follow-up Results: A total of 19 (70.4%) men and 8 (29.6%) women were evaluated. Mean age was 37.85Â±13.68 years. All three parameters had significant decrease in treatment course (p<0.001); however, no significant correlation was found between PASI and inflammatory biomarkers. Trends of ESR and CRP were significantly correlated in all patients (r=0.504, P =0.007) and males (r=0.739, P =0.036). Conclusion: Our study demonstrated that CRP and ESR decreased in Infliximab treatment, in accordance but non-regarded to PASI score decease. Regarding other studies results, using these biomarkers for treatment follow-up might need more caution. [GMJ. 2015;4(1):8-13]